GARANSI DAN PENERAPANNYA PERSPEKTIF HUKUM ISLAM - Hidayat, Taufiq (Islamic University of Indonesia, 2006)
The development of science and technology spur the human to be creative and later emerging various products. This is trigger the producers to plunge into competition to offer their products with various ways in order to their products to be in demand in the market. One of the ways is to give the best service to consumers with giving guarantee. In one side, guarantee is useful as an appeal for consumers, in the other side, it is useful for consumers to protect their rights. This paper will be focused on guarantee and its application according to Islamic perspective. The course include definition, functions and purposes, benefits, and lastly closing. In the Islamic law treasure have been acquainted with khiyar aib which the substance is same with the guarantee. The guarantee agreement according to Islam is allowed to achieve the human benefits and equality in Islamic economics. Such that application of the guarantee agreement have to revere the muâamalahâs principle namely equality.